Student's engagemen in English language learning by using Quizizz at senior high school - dwita putri, fanny; Rika Afriyanti; Melvina (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This study investigated students’ engagement in English learning using Quizizz at SMAN 15 Padang. Using a qualitative approach, this study explored aspects of behavioral, cognitive, emotional, academic, and social engagement. Data were collected through classroom observations, field notes, and video recordings. The findings revealed that Quizizz significantly increased students’ engagement by providing an interactive and enjoyable learning experience. Behavioral engagement was reflected in active participation and persistence during Quizizz sessions. Cognitive engagement was evident in students’ ability to critically analyze and discuss learning materials. Emotional engagement was demonstrated through students’ enthusiasm and satisfaction. While academic engagement demonstrated consistent progress in class, social engagement highlighted collaboration and interaction among peers and teachers. These results suggest that Quizizz can enhance English learning by encouraging greater student engagement. engagement.